Cultural competence of nursing educators at medical universities of 2nd regional planning in Iran - Sahand Majnoon; Vivian M. Yates; Hossein Asgarpour; Ahmad Mirza Aghazadeh Attari; Mojgan Lotfi (BMC Medical Education, 2023)
Abstract Background One of the facets of nursing care, as a holistic profession, is cultural care. Considering the role of culture in individuals’ health behaviors, nurses are recommended to be mindful of cultural care. Since nursing educators should be culturally competent to teach cultural care to students, this study aimed to determine the cultural competence of nursing educators of medical sciences universities in the 2nd regional planning in Iran. Methods The current research was a descriptive and survey study framed within Campinha-Bacote’s cultural competency model. All nursing educators of universities of medical sciences in the 2nd regional planning of Iran (Tabriz, Urmia, Ardabil, Khoy, Maragheh, Sarab, and Khalkhal) were considered as research units, and the cultural diversity questionnaire for nursing faculties (CDQNE-R) was sent to them. Out of 129 questionnaires sent, 84 were turned back. The data were analyzed by the SPSS 22 software. Results The results of this study showed that the research participants agreed with the subscales of cultural awareness, cultural knowledge, cultural skill, and cultural desire according to Sealey and Yates’ interpretation scale. Also, the research units cast doubts on the cultural encounter subscale. The mean scores of the participants’ responses to the questions of every subscale equaled 4.11, 3.52, 3.71, 3.38, and 3.93 for the subscales of cultural awareness, cultural knowledge, cultural skill, cultural encounter, and cultural desire, respectively. Likewise, the mean scores of participants’ responses to the subscales of transcultural educational behaviors and general cultural competence equaled 3.90 and 3.73. Conclusions The nursing faculties participating in the present study agreed with the 4 sub-models of Campinha-Bacote cultural care and the presence of cultural competence criteria. Also, the research units had doubts about the cultural encounter subscale. This result means that the research participants were undecided about their level of participation in face-to-face interactions with people from different cultural, racial, and ethnic groups. According to the results of the study, it is important to hold transcultural nursing training workshops and courses to maintain and improve the level of cultural competence of nursing faculties at universities of medical sciences in the 2nd regional planning in Iran.